The Endogenous Determination of Minimum Wage - Gil S. Epstein; Shmuel Nitzan (Institute for the Study of Labor (IZA), 1999)
In this paper we study the endogenous determination of minimum wage employing a political-economic game-theoretic approach. A major objective of the paper is to clarify the crucial role of the strength of the workers? union and of political culture on the determination of the minimum wage. In general, the equilibrium minimum wage differs from that postulated in the literature. In our uncertain environment the optimal minimum wage from the workers? union point of view is lower than the level that maximizes its objective function in a certain environment where there is no opposition to the proposed minimum wage. We establish that a political culture that assigns a positive weight to the public well being can give rise to a wage that equals or exceeds these levels.
Keywords: J38; J5; J3; 330; Minimum wage; endogenous determination; political culture; public policy; Mindestlohn; Public Choice; Spieltheorie; Gewerkschaftlicher Organisationsgrad; Politische Kultur; Theorie